Meta-Analysis of the Effect of Overexpression of Dehydration-Responsive Element Binding Family Genes on Temperature Stress Tolerance and Related Responses - Dong, Chao; Ma, Yuanchun; Zheng, Dan; Wisniewski, Michael; Cheng, Zong-Ming (Frontiers in Plant Science, 2018)
Dehydration-responsive element binding proteins are transcription factors that play a critical role in plant response to temperature stress. Over-expression of DREB genes has been demonstrated to enhance temperature stress tolerance. A series of physiological and biochemical modifications occur in a complex and integrated way when plants respond to temperature stress, which makes it difficult to assess the mechanism underlying the DREB enhancement of stress tolerance. A meta-analysis was conducted of the effect of DREB overexpression on temperature stress tolerance and the various parameters modulated by overexpression that were statistically quantified in 75 published articles. The meta-analysis was conducted to identify the overall influence of DREB on stress-related parameters in transgenic plants, and to determine how different experimental variables affect the impact of DREB overexpression. Viewed across all the examined studies, 7 of the 8 measured plant parameters were significantly (p≤ 0.05) modulated in DREB-transgenic plants when they were subjected to temperature stress, while 2 of the 8 parameters were significantly affected in non-stressed control plants. The measured parameters were modulated by 32% or more by various experimental variables. The modulating variables included, acclimated or non-acclimated, type of promoter, stress time and severity, source of the donor gene, and whether the donor and recipient were the same genus. These variables all had a significant effect on the observed impact of DREB overexpression. Further studies should be conducted under field conditions to better understand the role of DREB transcription factors in enhancing plant tolerance to temperature stress.